Nutritional and Biological Evaluation of Marine Seaweed as a Feedstuff and as a Pellet Binder in Poultry Diet - El-Deek, A.A.; Brikaa, Mervat A. (International Journal of Poultry Science, 2009)
The aim of this research was to evaluate the nutritional value of seaweed as a feedstuff for poultry and evaluate the use of seaweed as pellet binder in duck diets. Chemical analyses of dried marine red seaweed (Polysiphonia SPP) showed reasonable amounts of protein (32.4%); ether extract (17.7%), crude fiber (14.9%), ash (6.0%) and nitrogen free extract (23.4%). Seaweed contained appropriate amounts of minerals required by poultry. Leucine and lysine were the most abundant amino acids in seaweed protein. The content of each amino acid in seaweed protein is lower than the whole egg protein. Methionine is the first limiting amino acid (with chemical score 50.0%), valine and arginine were the second and third limiting amino acids in seaweed protein (with chemical score 71.63 and 74.33%, respectively). The estimation of Essential Amino Acid Index (EAAI) was 63.34% and the average of Total Protein Efficiency (TPE) value is 1.26. Thus seaweed is an intermediate source of protein for growing chicks. The metabolizable energy value of marine seaweed was 3518 kcal/kg. Seaweed up to 3% as a pellet binder did not adversely influence growth performance of ducks. Also, the physical test showed some improvement in pellet hardness quality. The inclusion of seaweed meal in the diet for ducks had no significant effects on all of carcass traits. In conclusion, seaweed is a valuable feed resource for poultry feeding and can be utilized as a pellet binder in duck diets.